Faktor-Faktor yang Mempengaruhi Penggunaan Kontrasepsi Hormonal Suntik 3 Bulan - Is Susiloningtyas; Friska Realita; Fira Nur Hasna (Syntax Corporation Indonesia, 2023)
The Family Planning (KB) program is a program to control the rate of population growth in order to meet the public's demand for better and better quality reproductive health (KR) services. The family planning program does not only aim to control the rate of population growth, but also to meet the demands of the community for quality family planning and reproductive health (KR) services, reduce the maternal mortality rate (MMR) and infant mortality rate (IMR) and improve reproductive health which aims to form a nice little family. Injectable contraception is a method of preventing pregnancy with hormonal injections. Injectable birth control is one of the most widely used methods of preventing pregnancy in Indonesia. Reviewing the literature regarding the factors that influence the use of 3-month injectable hormonal contraception. The method of writing this article is a literature review found in medical journal databases such as PubMed and Google Scholar. The results of the study showed that there was a significant relationship between the factors that influenced the 3-month injectable hormonal contraception. Based on the articles that have been collected, the results of the study show that age, education level, and husband's support are the main factors influencing the use of 3-month injection contraceptives. Based on the results of the discussion above, it can be concluded that the factors that influence the use of 3-month injections are influenced by 1). Age factor, 2). Weight gain factor 3) Husband support factor, 4) Education factor.